Presentation: Gilles Deleuze: at 100 years of his birth, 30 of his death (Tábano, 2025)
This year at Tábano we have prepared a special issue that wishes to highlight a significant moment in the field of philosophy and critical theory: the 30th anniversary of the death of Gilles Deleuze and the 100th anniversary of his birth. As a philosopher whose work continues to shape contemporary thought, Deleuze’s legacy is one that invites continual exploration and reinterpretation. This issue is dedicated to two primary aims: first, to delve deeply into the concepts that Deleuze developed throughout his extensive body of work, and second, to scrutinize how his thought is being recuperated, reinterpreted, and applied by contemporary philosophers.